Composite particles, method for producing same, electrode for electrochemical element, and electrochemical element

By forming a coating layer containing a fibrous conductive material on the surface of the active substance of the composite particles and controlling the ratio of envelope and specific surface area, the problem of insufficient resistance of the existing composite particles is solved, and sufficient reduction of resistance and improvement of electrochemical component performance is achieved.

CN119856290APending Publication Date: 2025-04-18ZEON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380059436.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-21
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing composite particles still have room for improvement in resistance, and it is difficult to achieve sufficiently low resistance.

Method used

The coating layer containing a fibrous conductive material is formed on the surface of the active material, and the ratio of the envelope degree and the BET specific surface area of ​​the coating layer are controlled in the coating layer formation step to form composite particles with sufficiently low resistance.

Benefits of technology

The resistance of composite particles is significantly reduced and the performance of electrochemical components is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides composite particles containing an active material having a coating layer containing a conductive material. The conductive material forming the conductive material-containing coating layer contains a fibrous conductive material. Furthermore, the composite particles are characterized in that the value of the ratio E2 / E1 of the envelope E2 of the active material having the conductive material-containing coating layer to the envelope E1 of the active material itself is 0.9999 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to composite particles and a method for producing the same, an electrode for an electrochemical element, and an electrochemical element. Background Art

[0002] Electrochemical devices such as lithium-ion secondary batteries have the characteristics of being small, lightweight, having high energy density, and being capable of repeated charge and discharge, and have been used in a wide range of applications.

[0003] In order to improve the performance of electrochemical elements, various improvements have been made to the materials forming the electrodes for electrochemical elements. The electrodes for electrochemical elements have a structure in which an electrode composite material layer is arranged on an electrode substrate, and the electrode composite material layer is mainly composed of an electrode active material and contains other components such as a conductive material and a binder material as needed to give the electrode unique functions such as conductivity, adhesion, and flexibility.

[0004] Among the materials for forming electrodes for electrochemical elements that have been improved in various ways in the past, particles whose surfaces are coated with carbon materials have been tried for electrode active materials (for example, see Patent Documents 1 to 3). Specifically, Patent Document 1 discloses a composite particle having a ceramic particle composed of a ceramic material that functions as an electrode active material, and a carbon layer formed on the surface of the ceramic particle. The carbon layer possessed by the composite particle has an amorphous portion of amorphous carbon and a granular graphite portion dispersed in the amorphous portion. In addition, Patent Document 2 discloses a composite particle in which a lithium-containing phosphate particle is coated with a carbon film, and the carbon film contains one or more carbon materials selected from (i) a fibrous carbon material, (ii) a chain carbon material, and (iii) a carbon material in which a fibrous carbon material and a chain carbon material are connected to each other. In addition, Patent Document 3 discloses the following technology: by applying a film-forming technology, a conductive film containing carbon and the like is formed on the surface of a positive electrode material particle, thereby reducing the internal resistance of the positive electrode.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2009-099287;

[0008] Patent document 2: International Publication No. 2013 / 073562;

[0009] Patent document 3: Japanese Patent Application Publication No. 2000-058063. Summary of the invention

[0010] Problem that the invention aims to solve

[0011] However, in existing composite particles, there is still room for further improvement in electrical resistance.

[0012] Therefore, an object of the present invention is to provide composite particles having sufficiently low electrical resistance and a method for producing the same.

[0013] Another object of the present invention is to provide an electrode for an electrochemical device including the composite particles, and an electrochemical device having the electrode for an electrochemical device.

[0014] Solutions for solving problems

[0015] The present inventors have conducted intensive research for the purpose of solving the above-mentioned problems. Then, the present inventors have newly discovered that by forming a coating layer containing a fibrous conductive material on at least a portion of the surface of an active material to satisfy a predetermined parameter related to the surface shape of the active material, and then compounding the obtained active material with the coating layer to form composite particles, composite particles with sufficiently low resistance can be obtained, thereby completing the present invention.

[0016] That is, the object of the present invention is to advantageously solve the above-mentioned problems. [1] The composite particles of the present invention are characterized in that they contain an active material, the active material has a coating layer containing a conductive material, the conductive material contains a fibrous conductive material, and the ratio E2 / E1 of the envelope E2 of the active material having the conductive material coating layer to the envelope E1 of the active material itself is 0.9999 or less. The electrical resistance of the composite particles satisfying such properties is sufficiently low.

[0017] Here, the "envelope" is a value calculated as the value obtained by dividing the envelope perimeter by the actual perimeter (perimeter envelope), and specifically, it can be measured by the method described in the examples of this specification. In addition, the ratio of the envelope E2 of the active material having a conductive material coating layer to the envelope E1 of the active material itself, that is, the ratio E2 / E1, can be calculated by the method described in the examples of this specification.

[0018] [2] In the composite particles of [1], it is preferred that the ratio S2 / S1 of the BET specific surface area S2 of the active material having the conductive material-containing coating layer to the BET specific surface area S1 of the active material itself is 1.5 or more. Composite particles satisfying this condition have lower electrical resistance.

[0019] Here, "BET specific surface area" refers to the nitrogen adsorption specific surface area measured by the BET method, and specifically, it can be measured by the method described in the examples of this specification. In addition, the ratio of the BET specific surface area S2 of the active material having the conductive material coating layer to the BET specific surface area S1 of the active material itself, that is, the ratio S2 / S1 can be calculated by the method described in the examples of this specification.

[0020] [3] The present invention aims to solve the above-mentioned problems advantageously. The method for producing composite particles of the present invention is characterized in that the composite particles contain active materials, the active materials have a coating layer containing a conductive material, and the method for producing composite particles comprises: a coating layer forming step, in which a fibrous conductive material and an active material having an envelope value of E1 are stirred and mixed to form an active material having a coating layer containing a conductive material; and a stirring granulation step, in which a plurality of active materials having a coating layer containing a conductive material are compounded while being stirred to form composite particles. In the coating layer forming step, the envelope value of the active material having the coating layer containing a conductive material is set to E2, and the value of the ratio E2 / E1 is 0.9999 or less. According to the method for producing composite particles of the present invention, the composite particles of the present invention having a sufficiently low resistance can be efficiently produced.

[0021] [4] Here, in the manufacturing method of [3], preferably, in the coating layer forming step, the ratio S2 / S1 of the BET specific surface area S2 of the active material having the conductive material-containing coating layer to the BET specific surface area S1 of the active material itself is 1.5 or more. According to the manufacturing method of the composite particles of the present invention, composite particles with lower resistance can be efficiently manufactured.

[0022] [5] In addition, the present invention aims to advantageously solve the above-mentioned problems. The electrode for an electrochemical element of the present invention is characterized in that it has an electrode composite material layer containing the composite particles for an electrochemical element described in [1] or [2] above.

[0023] [6] In addition, the present invention aims to advantageously solve the above-mentioned problems. The electrochemical device of the present invention comprises the electrode for an electrochemical device according to the above-mentioned [5].

[0024] Effects of the Invention

[0025] According to the present invention, composite particles having sufficiently low electrical resistance and a method for producing the same can be provided.

[0026] Furthermore, according to the present invention, there can be provided an electrode for an electrochemical device including the composite particles, and an electrochemical device having the electrode for an electrochemical device. DETAILED DESCRIPTION

[0027] Hereinafter, embodiments of the present invention will be described in detail.

[0028] Here, the composite particles of the present invention can be advantageously used as a compounding component of an electrode composite material layer of an electrode of an electrochemical device such as a secondary battery. In addition, according to the method for producing the composite particles of the present invention, the composite particles of the present invention can be efficiently produced.

[0029] (Composite particle)

[0030] The composite particles of the present invention contain an active material, and the above-mentioned active material has a coating layer containing a conductive material. Further, the composite particles are an aggregate of active materials. Moreover, the conductive material includes a fibrous conductive material. Furthermore, the composite particles are characterized in that the ratio E2 / E1 of the degree of envelope E2 of the active material having a coating layer containing a conductive material to the degree of envelope E1 of the active material itself is 0.9999 or less. Such composite particles having an active material with a coating layer containing a conductive material and satisfying a specified parameter for the surface shape have a sufficiently low resistance. Here, if the value of the ratio E2 / E1 is below the above upper limit value, it means that a part of the conductive material forming the coating layer containing the conductive material adheres to the surface in a convex shape. And it is presumed that a good conductive network can be formed in the composite particles through such a convexly adhering conductive material, and thus the resistance of the composite particles can be sufficiently reduced.

[0031] <Active material>

[0032] The active material (positive electrode active material, negative electrode active material) constituting the active material having a coating layer containing a conductive material is not particularly limited, and known electrode active materials can be used.

[0033] The positive electrode active material is not particularly limited, and examples thereof include lithium-containing cobalt oxides (lithium cobalt oxide, LiCoO 2 ), lithium manganese oxide (LiMn 2 O 4 ), lithium-containing nickel oxides (LiNiO 2 ), lithium-containing composite oxides of Co-Ni-Mn (Li(CoMnNi)O 2 ), lithium-containing composite oxides of Ni-Mn-Al, lithium-containing composite oxides of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO 4 ), olivine-type lithium manganese phosphate (LiMnPO 4 ), Li 2 MnO 3 -LiNiO 2 solid solution system, Li 1+x Mn 2-x O 4 (0 < X < 2)-represented lithium-excess spinel compound, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O 2 , LiNi 0.5 Mn 1.5 O 4Examples of the negative electrode active material include carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials in combination thereof.

[0034] The particle size of the electrode active material is preferably 0.03 μm or more, more preferably 0.1 μm or more, further preferably 0.5 μm or more, preferably 500 μm or less, more preferably 200 μm or less, and further preferably 30 μm or less. The particle size of the electrode active material can be measured by laser diffraction. More specifically, in the particle size distribution (volume basis) measured using a laser diffraction particle size distribution measuring device, the particle size D50 at which the cumulative volume calculated from the small particle size side becomes 50% is used as the volume average particle size, and it is preferred that this value meets the above-mentioned particle size range.

[0035] <Conductive Materials>

[0036] The conductive material containing the conductive material coating layer constituting at least a portion of the active material coated thereon comprises a fibrous conductive material. As the fibrous conductive material, there are no particular limitations, and there are single-layer or multi-layer carbon nanotubes, vapor-grown carbon fibers, carbon fibers obtained by carbonizing organic fibers, and their cuts, etc. These can be used alone or in combination of two or more. It is particularly preferred that the fibrous conductive material comprises a single-layer or multi-layer carbon nanotube. Furthermore, from the viewpoint of forming a good conductive network to further reduce the resistance of the composite particles, it is more preferred that the fibrous conductive material comprises a multi-layer carbon nanotube.

[0037] The average diameter of the fibrous conductive material contained in the conductive material is preferably 3 nm or more, more preferably 10 nm or more, more preferably 20 nm or more, preferably 200 nm or less, more preferably 100 nm or less, and more preferably 70 nm or less. If the average diameter of the fibrous conductive material is above the lower limit, a portion of the conductive material is easily attached to the surface in a convex shape, and a better conductive network can be formed. In addition, if the average diameter of the fibrous conductive material is below the upper limit, a good conductive network can be formed without excessively increasing the amount of conductive material.

[0038] In addition, the average length of the fibrous conductive material is preferably 1 μm or more, preferably 50 μm or less, and more preferably 25 μm or less. If the average length of the fibrous conductive material is within the above-specified range, a good conductive network can be formed by the fibrous conductive material, and the resistance of the composite particles can be further reduced.

[0039] The “average diameter of the fibrous conductive material” and the “average length of the fibrous conductive material” can be determined by measuring the diameter (outer diameter) and length of 100 randomly selected fibrous conductive material bodies, respectively, using a transmission electron microscope.

[0040] As the conductive material other than the above-described fibrous conductive material, there is no particular limitation, and a powdery conductive material such as carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace black, etc.) can be used. These can be used alone or in combination of multiple kinds. In addition, in the present specification, the fibrous conductive material and the powdery conductive material can be distinguished by the aspect ratio. That is, a conductive material having an aspect ratio of 10 or more is referred to as a fibrous conductive material, and a conductive material having an aspect ratio of less than 10 is referred to as a powdery conductive material.

[0041] Moreover, the content of the conductive material is not particularly limited. For example, based on the total mass of the composite particles, the content of the conductive material is preferably 0.5% by mass or more, more preferably 1.0% by mass or more, preferably 5% by mass or less, and more preferably 3% by mass or less. If the content of the conductive material in the composite particles is within the above range, the balance between the increase in the capacity and the decrease in the resistance of the obtained electrochemical element can be improved well.

[0042] <Degree of envelope>

[0043] Moreover, for the composite particles, the ratio E2 / E1 of the degree of envelope E2 of the active material having the conductive material-containing coating layer to the degree of envelope E1 of the active material itself needs to be 0.9999 or less. The value of the ratio E2 / E1 is preferably 0.9980 or less, and more preferably 0.9950 or less. Here, the degree of envelope is a value calculated in the form of a value obtained by dividing the envelope circumference by the actual circumference. Therefore, the more uneven the surface shape of the object, the smaller this value. The value of the ratio E2 / E1 being 0.9999 or less means that the surface shape of the active material having the conductive material-containing coating layer is more uneven than the degree of unevenness of the surface shape of the active material itself. In other words, it means that the conductive material-containing coating layer has an uneven shape. It is presumed that such an uneven conductive material-containing coating layer forms a good conductive network within the composite particles by contacting each other in the composite particles which are an aggregate of multiple active materials. Thus, when the value of the ratio E2 / E1 is below the above upper limit value, the resistance of the composite particles can be reduced well. In addition, the lower limit value of the ratio E2 / E1 is not particularly limited, and from the viewpoint of ease of manufacture, it is preferably 0.1000 or more, and more preferably 0.7000 or more.

[0044] <BET specific surface area ratio>

[0045] Furthermore, in the composite particles, the value of the ratio S2 / S1 of the BET specific surface area S2 of the active material having the conductive material coating layer relative to the BET specific surface area S1 of the active material itself is preferably 1.5 or more, more preferably 2.0 or more, and further preferably 2.5 or more. If the BET specific surface area is above the above lower limit, a good conductive network can be formed by the fibrous conductive material in the composite particles, which can further reduce the resistance. In addition, the upper limit of the value of the ratio S2 / S1 is not particularly limited, and from the viewpoint of ease of manufacture, it is preferably 60.0 or less, more preferably 40.0 or less, and further preferably 5.0 or less.

[0046] <Other ingredients>

[0047] In addition to the above-mentioned active material and conductive material, the composite particles may also contain a binding material. As the binding material, there is no particular limitation, and for example, conjugated diene polymers, acrylic polymers, aromatic vinyl block polymers, fluorine polymers, cellulose polymers, cyclic olefin polymers, etc. can be used. These can be used alone or in combination of two or more.

[0048] Conjugated diene polymer refers to a polymer comprising a conjugated diene monomer unit. Moreover, as a specific example of a conjugated diene polymer, it is not particularly limited, and copolymers such as styrene-butadiene copolymer (SBR) and the like comprising aromatic vinyl monomer units and aliphatic conjugated diene monomer units, butadiene rubber (BR), acrylic rubber (NBR) (a copolymer comprising acrylonitrile units and butadiene units), and their hydrides, etc. can be cited. In addition, the meaning of polymer "comprising monomer units" is "comprising structural units from monomers in the polymer obtained using the monomer".

[0049] The acrylic polymer is not particularly limited, and examples thereof include polymers containing crosslinking monomer units, (meth) acrylic acid ester monomer units, and acidic group-containing monomer units. In addition, the proportion of (meth) acrylic acid ester monomer units in the acrylic polymer is preferably 50% by mass or more, more preferably 55% by mass or more, further preferably 58% by mass or more, preferably 98% by mass or less, more preferably 97% by mass or less, and further preferably 96% by mass or less. In addition, in this specification, (meth) acrylic acid refers to acrylic acid or methacrylic acid.

[0050] As the aromatic vinyl block polymer, there can be mentioned a block polymer containing a block region composed of aromatic vinyl monomer units. As the aromatic vinyl monomer, there can be mentioned, for example, styrene, styrene sulfonic acid and its salts, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene, and styrene is particularly preferred. As the aromatic vinyl block polymer, there can be mentioned preferably styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene copolymers, and their hydrogenated products.

[0051] Fluorine-based polymers refer to polymers containing fluorine-containing monomer units and further containing monomers (non-fluorine-containing monomers) units that do not contain fluorine. As fluorine-containing monomers, there are no particular limitations, and examples thereof include vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, fluoroethylene, trifluoroethylene, chlorotrifluoroethylene, 2,3,3,3-tetrafluoropropylene, and perfluoroalkyl vinyl ethers. As fluorine-based polymers, there are no particular limitations, and examples thereof include polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, perfluoroalkoxy fluororesins, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, ethylene-chlorotrifluoroethylene copolymers, vinylidene fluoride-hexafluoropropylene copolymers (vinylidene fluoride-hexafluoropropylene copolymers), and the like.

[0052] The cellulose-based polymer is not particularly limited, and examples thereof include cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose.

[0053] The cyclic olefin polymer is not particularly limited, and examples thereof include polymers (addition polymers or ring-opening polymers) synthesized using cyclic olefin compounds as monomers and hydrides thereof, and hydrides of polymers using aromatic vinyl compounds as monomers. In order to easily adjust the electrolyte swelling degree and glass transition temperature to suitable values, hydrides of ring-opening polymers using cyclic olefin compounds as monomers and hydrides of polymers using aromatic vinyl compounds as monomers are particularly preferred.

[0054] The cyclic olefin compound is not particularly limited, and examples thereof include:

[0055] Norbornene, 5-methylnorbornene, 5-ethylnorbornene, 5-butylnorbornene, 5-hexylnorbornene, 5-decylnorbornene, 5-cyclohexylnorbornene, 5-cyclopentylnorbornene and other unsubstituted or alkyl-containing norbornenes;

[0056] Norbornenes having an alkenyl group, such as 5-ethylidene norbornene, 5-vinyl norbornene, 5-propenyl norbornene, 5-cyclohexenyl norbornene, and 5-cyclopentenyl norbornene;

[0057] Norbornenes with aromatic rings such as 5-phenylnorbornene;

[0058] Norbornenes having a polar group containing an oxygen atom, such as 5-methoxycarbonyl norbornene, 5-ethoxycarbonyl norbornene, 5-methyl-5-methoxycarbonyl norbornene, 5-methyl-5-ethoxycarbonyl norbornene, norbornenyl-2-methylpropionate, norbornenyl-2-methyloctanoate, 5-hydroxymethyl norbornene, 5,6-bis(hydroxymethyl)norbornene, 5,5-bis(hydroxymethyl)norbornene, 5-hydroxy-isopropyl norbornene, 5,6-dicarboxynorbornene, and 5-methoxycarbonyl-6-carboxynorbornene;

[0059] Norbornenes having a polar group containing a nitrogen atom, such as 5-cyanorbornene;

[0060] Dicyclopentadiene, methyl dicyclopentadiene, tricyclo[5.2.1.0 2,6 ] polycyclic norbornenes with three or more rings that do not contain an aromatic ring structure, such as dec-8-ene;

[0061] Four Rings [9.2.1.0 2,10 .0 3,8 ]tetradeca-3,5,7,12-tetraene (also known as 1,4-methano-1,4,4a,9a-tetrahydro-9H-fluorene), tetracyclo[10.2.1.0 2,11 .0 4,9 ] polycyclic norbornenes having three or more aromatic rings, such as 1,4-methano-1,4,4a,9,9a,10-hexahydroanthracene;

[0062] Tetracyclododecene, 8-methyltetracyclododecene, 8-ethyltetracyclododecene, 8-cyclohexyltetracyclododecene, 8-cyclopentyltetracyclododecene, 8-methoxycarbonyl-8-methyltetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene and other unsubstituted or alkyl-containing tetracyclododecenes;

[0063] Tetracyclododecenes having a double bond outside the ring, such as 8-methylenetetracyclododecene, 8-ethylenetetracyclododecene, 8-vinyltetracyclododecene, 8-propenyltetracyclododecene, 8-cyclohexenyltetracyclododecene, and 8-cyclopentenyltetracyclododecene;

[0064] Tetracyclododecenes having an aromatic ring, such as 8-phenyltetracyclododecene;

[0065] Tetracyclododecenes having a substituent containing an oxygen atom, such as 8-methoxycarbonyltetracyclododecene, 8-methyl-8-methoxycarbonyltetracyclododecene, 8-hydroxymethyltetracyclododecene, 8-carboxytetracyclododecene, tetracyclododecene-8,9-dicarboxylic acid, and tetracyclododecene-8,9-dicarboxylic anhydride;

[0066] Tetracyclododecenes having a substituent containing a nitrogen atom, such as 8-cyanotetracyclododecene and tetracyclododecene-8,9-dicarboxylic acid imide;

[0067] Tetracyclododecenes having a substituent containing a halogen atom, such as 8-chlorotetracyclododecene;

[0068] Tetracyclododecenes having a substituent containing a silicon atom, such as 8-trimethoxysilyltetracyclododecene;

[0069] Hexacyclic heptadecenes such as Diels-Alder adducts of the above-mentioned tetracyclic dodecenes and cyclopentadiene.

[0070] The content of the binder is not particularly limited. For example, based on the total mass of the composite particles, the content of the binder is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less. If the content of the binder in the composite particles is within the above range, the resistance of the composite particles can be effectively reduced.

[0071] (Method for producing composite particles)

[0072] The method for manufacturing composite particles of the present invention is a method for manufacturing composite particles containing active materials, wherein the active material has a coating layer containing a conductive material, and the method for manufacturing the composite particles comprises: a coating layer forming step, wherein a fibrous conductive material and an active material having an envelope value of E1 are stirred and mixed to form an active material having a coating layer containing a conductive material; and a stirring granulation step, wherein a plurality of active materials having a coating layer containing a conductive material are compounded while being stirred to form composite particles. Moreover, it is characterized in that in the coating layer forming step, the envelope of the active material having a coating layer containing a conductive material is set to E2, and the value of the ratio E2 / E1 is less than 0.9999. According to the method for manufacturing the composite particles, the composite particles of the present invention described above can be efficiently manufactured. Furthermore, the method for manufacturing the composite particles can also implement a pre-stirring step of further adding a conductive material to the active material having a coating layer containing a conductive material and mixing it between the coating layer forming step and the stirring granulation step. In addition, as the active material, conductive material, and binding material used in each step described in detail below, those described above can be used. In addition, each step described in detail below can be carried out in a stirring tank having a stirring member such as a stirring blade, for example.

[0073] <Coating Layer Forming Step>

[0074] In the coating layer forming step, the fibrous conductive material and the active material having an envelope value of E1 are stirred and mixed to form an active material having a conductive material coating layer. The fibrous conductive material can be pre-dispersed in a solvent and used in a dispersion state. As a solvent, there is no particular limitation as long as it is a solvent capable of dispersing the fibrous conductive material, and all solvents such as cyclohexane, n-hexane, acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, dichloromethane, and chloroform can be used. In addition, the dispersion of the fibrous conductive material can also arbitrarily contain a bonding material.

[0075] In the coating layer forming process, specifically, the active material is put into a stirring tank, and the stirring blade is rotated to make the active material in a stirring state, and then the dispersion of the fibrous conductive material is continuously or intermittently put in. As the method of putting in, there is no particular limitation, and examples include dropwise addition or spraying using a two-fluid nozzle, etc. Then, after the dispersion of the fibrous conductive material of the entire amount is put in, the rotation of the stirring blade is stopped to release the stirring state. In addition, when implementing the pre-stirring process as an arbitrary process, it is preferred to put in a part of the entire conductive material in this process.

[0076] The envelope value of the active material having the conductive material coating layer formed in the coating layer forming step is E2. Then, compared with the envelope value E1 of the active material itself before coating, the value of the ratio E2 / E1 is 0.9999 or less. In addition, the preferred range of the value of the ratio E2 / E1 is as described above.

[0077] In addition, the BET specific surface area value of the active material having the conductive material coating layer formed in the coating layer forming step is S2. In addition, from the viewpoint of further reducing the resistance, the value of the ratio S2 / S1 of the BET specific surface area S2 of the above-mentioned active material having the conductive material coating layer to the BET specific surface area S1 of the active material itself is preferably 1.5 or more. In addition, the preferred range of the value of the ratio S2 / S1 is as described above.

[0078] <Pre-mixing process>

[0079] In the pre-stirring process, a conductive material is further added to the active material having a conductive material coating layer formed in the above-mentioned coating layer forming process and mixed. For example, in the pre-stirring process, the active material having a conductive material coating layer can be stirred to make it a stirred state, and then the conductive material is added, or the active material having a conductive material coating layer and the conductive material can be put into a stirring tank, and then stirring is started. Then, at the end of the pre-stirring process, the mixture in the stirring tank is preferably in a dry state. In addition, in the case of not implementing the pre-stirring process, a conductive material can also be added to the active material having a conductive material coating layer in the stirring granulation process.

[0080] <Stirring and granulating process>

[0081] In the stirring granulation process, multiple active materials having a coating layer containing a conductive material are compounded while being stirred, thereby producing composite particles. Specifically, in the stirring granulation process, a binding material is added to the active material having a coating layer containing a conductive material and the conductive material in a stirred state, and multiple active materials are compounded in the binding material to obtain composite particles. Here, the binding material can be used in a state of a dispersion dissolved or dispersed in a solvent. There is no particular limitation on the solvent, and all solvents can be used as long as they can dissolve or disperse the above-mentioned binding material. As the solvent, cyclohexane, n-hexane, acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, dichloromethane, chloroform, etc. can be cited in particular. These can be used alone or in combination of two or more in any ratio.

[0082] Optionally, after the stirring granulation step is completed, a granulation step of stirring the powder material in the stirring tank to perform granulation.

[0083] (Electrode for electrochemical device)

[0084] The electrode of the present invention has at least an electrode composite material layer comprising the above-mentioned electrochemical element composite particles. The electrode composite material layer is arranged on at least one surface of the electrode substrate. Moreover, the electrode of the present invention has an electrode composite material layer comprising the composite particles of the present invention, so the resistance is sufficiently low. Moreover, by using this electrode, the electrochemical element can exert excellent output characteristics. In addition, the electrode of the present invention can be any one of the positive electrode and the negative electrode, but is particularly preferably a positive electrode.

[0085] <Electrode Base Material>

[0086] As the electrode substrate, a material having conductivity and electrochemical durability can be used. Specifically, as the electrode substrate, a current collector formed of, for example, iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. In addition, the above materials can be used alone or in combination of two or more in any ratio.

[0087] <Method for producing an electrode for an electrochemical device>

[0088] The electrode for an electrochemical device can be produced by pressure-molding the composite particles of the present invention described above on an electrode substrate to form an electrode composite material layer.

[0089] The compression molding can be carried out according to known methods. For example, by supplying the above-mentioned composite particles to a roller press and rolling them on the electrode substrate, the composite particles can be compression molded on the electrode substrate to form an electrode composite material layer. The pressure during compression can be appropriately set according to the target electrode density.

[0090] (Electrochemical Components)

[0091] Furthermore, the electrochemical element formed using the electrochemical element electrode of the present invention is not particularly limited, and can be, for example, a lithium ion secondary battery, a double electric layer capacitor, or a lithium ion capacitor, and can be preferably a lithium ion secondary battery. The electrochemical element formed using the electrochemical element electrode of the present invention has low internal resistance and excellent output characteristics.

[0092] Here, the following describes the case where the electrochemical element is a lithium ion secondary battery as an example, but the present invention is not limited to the following example. The lithium ion secondary battery as the electrochemical element of the present invention generally has electrodes (positive electrode and negative electrode), an electrolyte, and a separator, and at least one of the positive electrode and the negative electrode uses the electrode for the electrochemical element of the present invention.

[0093] <Electrode>

[0094] Here, as an electrode other than the above-mentioned electrode for electrochemical element of the present invention that can be used in a lithium ion secondary battery as an electrochemical element, it is not particularly limited, and a known electrode can be used. Specifically, as an electrode other than the above-mentioned electrode for electrochemical element, an electrode formed by forming an electrode composite material layer on a current collector using a known manufacturing method can be used. In addition, the electrochemical element preferably has the above-mentioned electrode for electrochemical element of the present invention as a positive electrode.

[0095] <Electrolyte>

[0096] As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent can be generally used. As the supporting electrolyte, for example, a lithium salt can be used. Examples of the lithium salt include LiPF 6 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlCl 4 、LiClO 4 CF 3 SO 3 Li, C 4 F 9 SO 3 Li, CF 3 COOLi, (CF 3 CO) 2 NLi, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2 )NLi, etc. LiPF is particularly preferred because it is easily soluble in solvents and exhibits a high degree of dissociation. 6 、LiClO 4 CF 3 SO 3 Li, particularly preferably LiPF 6 In addition, the electrolyte may be used alone or in combination of two or more at any ratio.

[0097] As an organic solvent used in the electrolyte, there is no particular limitation as long as it can dissolve the supporting electrolyte. For example, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC) can be preferably used; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used. In addition, the concentration of the electrolyte in the electrolyte can be appropriately adjusted. In addition, known additives such as vinylene carbonate, fluoroethylene carbonate, ethyl methanesulfonate, etc. can also be added to the electrolyte.

[0098] <Spacer>

[0099] As a spacer, there is no particular limitation, and known spacers can be used. In particular, a microporous membrane formed by a polyolefin resin (polyethylene, polypropylene, polybutylene, polyvinyl chloride) is preferred. Furthermore, as a spacer, a spacer with a functional layer having a functional layer (porous membrane layer or adhesive layer) provided on one or both sides of the spacer substrate can also be used.

[0100] <Method for producing lithium-ion secondary battery>

[0101] Lithium ion secondary batteries can be manufactured by, for example, the following methods: overlapping the positive electrode and the negative electrode across a spacer, winding and folding the battery as needed according to the shape of the battery, and then placing the battery container, injecting electrolyte into the battery container, and sealing. In order to prevent the internal pressure of the secondary battery from rising, overcharging and discharging, etc., fuses, PTC elements and other anti-overcurrent elements, porous metal mesh, guide plates, etc. can be provided as needed. The shape of the secondary battery can be, for example, any one of a coin shape, a button shape, a sheet shape, a cylindrical shape, a square shape, a flat shape, etc.

[0102] Example

[0103] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0104] Furthermore, unless otherwise specified, in a polymer produced by copolymerizing a plurality of monomers, the ratio of a repeating unit (monomer unit) formed by polymerizing a certain monomer in the above polymer is generally consistent with the ratio (feed ratio) of the certain monomer in all monomers used for the polymerization of the polymer.

[0105] In the examples and comparative examples, the measurement and evaluation of various properties were carried out according to the following methods. In addition, the aspect ratio of the fibrous conductive materials used in the examples and comparative examples was 10 or more, and the aspect ratio of the powdery conductive materials was less than 10.

[0106] <Value of perimeter envelope ratio E2 / E1>

[0107] Using "Morphologi G3" manufactured by Malvern, binary processing and analysis were performed on the images of 10,000 active substances (active substances with a conductive material coating layer and active substances before forming the coating layer) used in each example and comparative example, and the average value of the perimeter envelope degree was obtained. Specifically, for the 10,000 active substances as the objects, the average value of the value obtained by dividing the perimeter of the convex circumscribed figure (minimum convex hull) by the actual perimeter P was taken, and this value was used as the average perimeter envelope degree. Based on the average value E1 of the perimeter envelope degree of the active substance before forming the coating layer (i.e., the active substance itself) and the average value E2 of the perimeter envelope degree of the active substance with a conductive material coating layer obtained in this way, the ratio E2 / E1 was calculated.

[0108] <Value of BET specific surface area ratio S2 / S1>

[0109] Using a specific surface area and pore size distribution measuring device (BELSORP-miniII, manufactured by MicrotracBEL Corp.), the nitrogen adsorption isotherm at 77K was measured and analyzed by the BET method, and thus the BET specific surface area of each active substance (active substance with a conductive material coating layer and active substance before forming the coating layer) used in each example and comparative example was obtained. The pretreatment was carried out under reduced pressure at 150 °C for 20 minutes. The BET specific surface area was measured by filling 5 g of each active substance in a test tube. Based on the values of the BET specific surface area S1 of the active substance before forming the coating layer (i.e., the active substance itself) and the BET specific surface area S2 of the active substance with a conductive material coating layer obtained in this way, the ratio S2 / S1 was calculated.

[0110] <Resistance of composite particles>

[0111] Using a powder resistance measurement system (MCP-PD51 type; manufactured by Dia Instruments), the resistance value was measured while continuously applying pressure to the composite particles manufactured in the examples and comparative examples. Based on the resistance value R (Ω) converging with respect to the pressure and the area S (cm 2) and thickness d (cm) to calculate the resistivity ρ (Ω·cm) = R × (S / d). For each measurement result at a load of 20 kN in each embodiment and comparative example, the value of (each embodiment to comparative example) / (Comparative Example 1) was calculated based on the measurement result in Comparative Example 1, and evaluated as the ratio of the resistance value in each example based on the measurement result in Comparative Example 1. The smaller the ratio value obtained in this way, the lower the resistance.

[0112] (Example 1)

[0113] <Manufacturing of adhesive materials>

[0114] 270 parts of dehydrated cyclohexane, 0.53 parts of ethylene glycol dibutyl ether, and 0.47 parts of n-butyl lithium (15% cyclohexane solution) were placed in a reactor with a stirring device and fully substituted with nitrogen. While stirring all the contents at 60°C, 12.5 parts of dehydrated styrene were continuously added to the reactor over 40 minutes. After the addition was completed, the entire contents were further stirred at 60°C for 20 minutes. The reaction solution was measured by gas chromatography, and the polymerization conversion rate at this moment was 99.5%. Next, 75.0 parts of dehydrated isoprene were continuously added to the reaction solution over 100 minutes, and stirring was continued for 20 minutes after the addition was completed. The polymerization conversion rate at this moment was 99.5%. Thereafter, 12.5 parts of dehydrated styrene were continuously added over 60 minutes, and the entire contents were stirred for 30 minutes after the addition was completed. The polymerization conversion rate at this moment was approximately 100%.

[0115] Here, 0.5 parts of isopropanol were added to the reaction solution to terminate the reaction. The obtained polymer solution was transferred to a pressure-resistant reactor with a stirring device, and 7.0 parts of a diatomaceous earth-supported nickel catalyst (manufactured by JGC Catalysts & Chemicals, product name "E22U", nickel loading 60%) and 80 parts of dehydrated cyclohexane were added as a hydrogenation catalyst and mixed. The interior of the reactor was replaced with hydrogen, and hydrogen was supplied while stirring the solution, and the hydrogenation reaction was carried out at a temperature of 190°C and a pressure of 4.5 MPa for 6 hours.

[0116] After the hydrogenation reaction was completed, the reaction solution was filtered to remove the hydrogenation catalyst, and then 1.0 part of a xylene solution in which 0.1 part of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (manufactured by Koyo Chemical Research Institute Co., Ltd., product name "Songnox 1010") as a phenolic antioxidant was dissolved was added to the filtrate to dissolve it. Cyclohexane was then added to prepare a binder material solution having a solid content concentration of 10% by mass.

[0117] <Production of composite particles>

[0118] <<Preparation process>>

[0119] First, a predetermined amount of active material and a CNT (carbon nanotube) dispersion as a fibrous conductive material dispersion are prepared. Specifically, as an active material, NMC532 (average particle size 6 μm) as a positive electrode active material for lithium-ion batteries is prepared. In addition, as CNT, multilayer CNT (average diameter: 50 nm, average length: 15 μm) is used. Furthermore, using the binder prepared as described above, the multilayer CNT and the binder are dispersed in cyclohexane at a solid content concentration of 1.0 mass % to prepare a fibrous conductive material dispersion. In this preparation, the ratio of the active material, the fibrous conductive material, and the binder is 97:1:0.1 on a mass basis.

[0120] <<Coating layer forming step>>

[0121] The following composite particle production device is prepared: in a cylindrical container with an inner diameter of 180 mm and a content of 2 L as a stirring tank, the axial direction of the cylindrical container is the vertical direction, and stirring blades are provided on two axes in the vertical direction and the horizontal direction (the vertical direction is the main stirring blade, and the horizontal direction is the auxiliary stirring blade). In addition, the main stirring blade has an inclined paddle blade with three main blades with a diameter of 170 mm, the auxiliary stirring blade has a V-shaped anchor blade with a diameter of 30 mm, and the structure is sealed by passing air to prevent raw materials from mixing into the driving parts of the main stirring blade and the auxiliary stirring blade. Various processes are implemented using a device with such a structure to produce composite particles.

[0122] First, the entire amount of active material prepared in the above process is added to the stirring tank, and the circumferential speed of the main stirring part is 6m / s and the circumferential speed of the auxiliary stirring part is 5m / s. For the active material in the stirring state, the fibrous conductive material dispersion prepared in the above process is added from the two-fluid nozzle. The stirring state is continued until the addition of the fibrous conductive material dispersion is completed. After the addition is completed, the stirring is stopped, and the active material having a conductive material coating layer is taken out, and the perimeter envelope and BET specific surface area are measured as described above.

[0123] <<Pre-mixing process>>

[0124] In the pre-mixing step, the entire amount of the active material having the conductive material coating layer formed in the coating layer forming step and 1 part of carbon black (BET specific surface area: 62 m 2 / g, bulk density 0.16g / cm 3) was put into a stirring tank. Then, the stirring portion sealing air was circulated at 20 L / min (ventilation volume 10 / min), and stirring was performed for 15 minutes under the operating conditions that the peripheral speed of the main stirring portion was 5 m / s and the peripheral speed of the auxiliary stirring portion was 6 m / s.

[0125] <<Stirring and granulating process>>

[0126] In the stirring granulation process, the air used to seal the stirring section was circulated at 20 L / min (air flow rate 10 / min). Under the operating conditions of the circumferential speed of the main stirring section being 5 m / sec and the circumferential speed of the auxiliary stirring section being 6 m / sec, a binder solution having a solid content of 0.9 parts by mass (solid content concentration 10 mass %, viscosity 200 mPa·s, solvent: cyclohexane) was continuously added for 15 minutes.

[0127] Next, the stirring section sealing air was circulated at 20 L / min (air flow rate 10 / min), and the operation was carried out for 10 minutes under the operating conditions of the peripheral speed of the main stirring section at 2 m / s and the peripheral speed of the auxiliary stirring section at 2 m / s. The prepared composite particles were evaluated as described above.

[0128] (Example 2)

[0129] Composite particles were prepared in the same manner as in Example 1, and the resistance was measured and evaluated, except that the stirring conditions in the coating layer forming step were changed so that the values ​​of the perimeter envelope ratio E2 / E1 and the BET specific surface area ratio S2 / S1 were as shown in Table 1. The results are shown in Table 1.

[0130] (Example 3)

[0131] In the pre-stirring step, the conductive material added was changed from carbon black as a powdered conductive material to 1 part of a fibrous conductive material dispersion (a material prepared in the same manner as the material prepared in the preparation step of Example 1) in terms of solid content. In the pre-stirring step, the fibrous conductive material dispersion was continuously added during the operation time of the stirring section.

[0132] In addition, the amount of the binder added in the stirring granulation step was adjusted so that the ratio of each component contained in the obtained composite particles would be as shown in Table 2.

[0133] Composite particles were prepared in the same manner as in Example 1 except for these points, and the electrical resistance was measured and evaluated. The results are shown in Table 1.

[0134] (Example 4)

[0135] Composite particles were prepared in the same manner as in Example 3 except that the stirring conditions in the coating layer forming step were changed so that the values ​​of the perimeter envelope ratio E2 / E1 and the BET specific surface area ratio S2 / S1 were as shown in Table 1. The electrical resistance was measured and evaluated. The results are shown in Table 1.

[0136] (Comparative Example 1)

[0137] In the preparation step, carbon black (BET specific surface area: 62 m 2 / g, bulk density 0.16g / cm 3 ) was used instead of the fibrous conductive material, and the coating layer forming step was not performed. The pre-stirring step of Example 1 was performed in the same manner as in Example 1, and 97 parts of the active material NMC532 (average particle size 6 μm) without a coating layer and 2 parts of the powdered conductive material were mixed. In addition, the amount of the binder in the composite particles was changed to 1 part in terms of the solid content. The stirring granulation step was performed in the same manner as in Example 1 to obtain composite particles, and the resistance was measured and evaluated. The results are shown in Table 1.

[0138] In addition, since the composite particles used in this example do not have a coating layer, the value of the perimeter envelope ratio E2 / E1 is set to 1.0000, and the value of the BET specific surface area ratio S2 / S1 is set to 1.0.

[0139] (Comparative Example 2)

[0140] In the preparation step, in addition to the fibrous conductive material, carbon black (BET specific surface area: 62 m 2 / g, bulk density 0.16g / cm 3 ), and no coating layer forming process was performed. The pre-stirring process was performed in the same manner as in Example 1, and 97 parts of active material NMC532 (average particle size 6 μm) without a coating layer, 1 part of a powdered conductive material, and 1 part of a fibrous conductive material dispersion in terms of solid content were mixed. In addition, in the pre-stirring process, the fibrous conductive material dispersion was continuously added during the operating time of the stirring section. Moreover, the amount of the binding material in the composite particles was made 1 part in terms of solid content. Other than this, the stirring and granulation process was performed in the same manner as in Example 1 to obtain composite particles, and the resistance was measured and evaluated. The results are shown in Table 1.

[0141] In addition, the composite particles used in this example also did not have a coating layer similarly to Comparative Example 1, and therefore the value of the perimeter envelope ratio E2 / E1 was set to 1.0000, and the value of the BET specific surface area ratio S2 / S1 was set to 1.0.

[0142] (Comparative Example 3)

[0143] In the preparation step, in addition to the fibrous conductive material, carbon black (BET specific surface area: 62 m 2 / g, bulk density 0.16g / cm 3 ), without combining with fibrous conductive materials to produce composite particles.

[0144] In the coating layer forming process, the conductive material is not added through the two-fluid nozzle. 97 parts of active material and 1 part of powdered conductive material are added to the stirring granulator, and stirring is started under the same conditions as in Example 1. To the active material and powdered conductive material in the stirring state, 0.1 parts of a binder solution (solid content concentration 10% by mass, viscosity 200 mPa·s, solvent: cyclohexane) is continuously added from the two-fluid nozzle.

[0145] In the pre-mixing step, the entire amount of the active material having the coating layer containing the powdery conductive material obtained in the above step and 1 part of carbon black (BET specific surface area: 62 m 2 / g, bulk density 0.16g / cm 3 ) was put into a stirring tank. Then, stirring was performed under the same conditions as in Example 1.

[0146] Then, in the stirring granulation step, 0.9 parts of a binder solution (solid content concentration 10 mass %, viscosity 200 mPa·s, solvent: cyclohexane) was continuously added in terms of solid content, and the same procedure as in Example 1 was followed to produce composite particles. The resistance of the produced composite particles was measured and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0147] [Table 1]

[0148]

[0149] As can be seen from Table 1, the composite particles of Examples 1 to 4 having a ratio E2 / E1 of the envelope E2 of the active material having the conductive material-containing coating layer to the envelope E1 of the active material itself of 0.9999 or less have sufficiently low resistance.

[0150] On the other hand, it is found that the composite particles of Comparative Examples 1 to 3 which do not have the predetermined conductive material-containing coating layer have high electrical resistance.

[0151] Industrial Applicability

[0152] According to the present invention, composite particles having sufficiently low electrical resistance and a method for producing the same can be provided.

[0153] Furthermore, according to the present invention, there can be provided an electrode for an electrochemical device including the composite particles, and an electrochemical device having the electrode for an electrochemical device.

Claims

1. A composite particle comprising an active material, wherein the active material has a coating layer containing a conductive material, The conductive material comprises a fibrous conductive material, A value of a ratio E2 / E1 of an envelope degree E2 of the active material having the conductive material-containing coating layer to an envelope degree E1 of the active material itself is 0.9999 or less.

2. The composite particles according to claim 1, wherein The value of a ratio S2 / S1 of a BET specific surface area S2 of the active material having the conductive material-containing coating layer to a BET specific surface area S1 of the active material itself is 1.5 or more.

3. A method for producing composite particles, wherein the composite particles contain an active material, the active material having a coating layer containing a conductive material, The method for producing the composite particles comprises: a coating layer forming step of stirring and mixing the fibrous conductive material and the active material having an envelope value of E1 to form an active material having a conductive material coating layer; as well as a stirring granulation step of compounding the plurality of active materials having the conductive material coating layer while stirring them to form composite particles; In the coating layer forming step, the envelope of the active material having the conductive material-containing coating layer is set to E2, and the value of the ratio E2 / E1 is 0.9999 or less.

4. The method for producing composite particles according to claim 3, wherein: In the coating layer forming step, a value of a ratio S2 / S1 of a BET specific surface area S2 of the active material having the conductive material-containing coating layer to a BET specific surface area S1 of the active material itself is 1.5 or more. 5 . An electrode for an electrochemical device, comprising an electrode composite material layer comprising the composite particles according to claim 1 or 2. 6 . An electrochemical device comprising the electrode for an electrochemical device according to claim 5 .

Citation Information

Patent Citations

  • Lithium secondary battery having high conductive positive electrode and manufacture thereof

    JP2000058063A

  • Electrode material powder for secondary battery, and manufacturing method thereof

    JP2009099287A

  • Composite particles, method for producing same, electrode material for secondary batteries, and secondary battery

    WO2013073562A1